Mechanisms of Morality: Sources of Support for Humanitarian Intervention. (September 2018) - Kreps, Sarah; Maxey, Sarah
Humanitarian interventions (HIs) are a common aspect of US foreign policy. Policy makers acknowledge the importance of public support for interventions, but scholars remain divided about the extent and basis of that support. Using a series of survey experiments, we evaluate attitudes about HIs, assess whether the public supports these interventions for instrumental or moral reasons, and test which aspects of morality are most salient. The findings indicate that interventions addressing humanitarian crises boost public support, with the basis of that support residing primarily in normative contentions that the United States has a moral obligation to protect civilians. This research advances understandings of morality in foreign policy, mediates debates about the determinants of public attitudes—including when the public makes moral rather than prudent decisions about interventions—and has important policy implications. It suggests a morally motivated public may be more likely to support risky HIs, increasing the likelihood of using force.